3D4Ever: why is it so hard to talk about the preservation of 3D data?. Issue 2 (4th May 2017) - Kilbride, William
Abstract: This brief opinion piece reflects on the author's experience planning the programme for a conference on 3D data: '3D4ever: building three dimensional models to last'. The development of 3D laser scanning and printing technology in recent years is described and the author laments the apparent lack of attention to the long-term preservation of the resulting data. While the agencies involved in creating 3D data do seem to understand the long-term value of the data, they have not taken sufficient action to ensure the value is maintained. In this article a challenge is posed to address the gap between the communities who create 3D data and those with the expertise to manage and preserve it for the long-term.